2014
DOI: 10.1634/theoncologist.2013-0286
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Management of Infusion-Related Reactions in Breast Cancer Patients Receiving Trastuzumab

Abstract: Identify risk factors associated with trastuzumab-associated infusion-related reactions.Describe the impact of premedications on the incidence and/or severity of trastuzumab-associated infusion-related reactions. ABSTRACTBackground. Trastuzumab has become a mainstay of therapy for human epidermal growth factor receptor-2 overexpressed breast cancer in nearly all stages of the disease. Like many monoclonal antibodies, trastuzumab is associated with infusionrelated reactions (IRRs) that are not well described, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
4
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 14 publications
2
43
4
11
Order By: Relevance
“…Certain patients can manifest with nausea, chills, fever, and malaise [7,25,26]. For trastuzumab, typical first-time infusion reactions include chills and/or fever and occur in approximately 40 % of patients [27]. These are thought to be due to the release of proinflammatory cytokines (such as IL-6 and TNF-α) and do not tend to be severe, except for the findings of the anti-CD28 mAb TGN1412 phase 1 trial in which six volunteers who received the drug developed multiorgan failure as a result of a severe cytokine storm [28].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Certain patients can manifest with nausea, chills, fever, and malaise [7,25,26]. For trastuzumab, typical first-time infusion reactions include chills and/or fever and occur in approximately 40 % of patients [27]. These are thought to be due to the release of proinflammatory cytokines (such as IL-6 and TNF-α) and do not tend to be severe, except for the findings of the anti-CD28 mAb TGN1412 phase 1 trial in which six volunteers who received the drug developed multiorgan failure as a result of a severe cytokine storm [28].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Typical first-time infusion reactions for trastuzumab include chills and/or fever and occur in approximately 40 % of patients [36]. These are thought to be due to the release of proinflammatory cytokines (such as IL-6 and TNF-α) and do not tend to be severe, except for the findings of the of the anti-CD28 monoclonal antibody TGN1412 phase 1 trial in which six volunteers who received the drug developed multiorgan failure as a result of a severe cytokine storm [37].…”
Section: Desensitization To Monoclonal Antibodiesmentioning
confidence: 99%
“…Onset of mild-to-moderate symptoms such as chills, fever, hypotension and dyspnoea are classified as an IRR; these symptoms are poorly defined and so lead to a variation in IRR rates in the literature. A retrospective review of 197 patients demonstrated IRR in 16% and anaphylaxis in 1% 9. A large retrospective analysis of 25 000 patients shows anaphylaxis in 0.3% of patients 10.…”
Section: Introductionmentioning
confidence: 99%